A Day in the Life of a Doctor Working at The Himalayan Rescue Association. Issue 1 (1st March 2011) - Stokes, Suzy; Mackenzie, S
Abstract : The Himalayan Rescue Association's (HRA) clinic in Pheriche, Nepal (4243m) is one of a number of high altitude medical posts where demands for services are increasing. Every year international doctors see over 1000 patients, assisting local people with basic health needs and providing emergency care for trekkers with both altitude-related and general illnesses and injuries. This article describes the work of the voluntary clinic and some of the challenges it faces.